Carbon Stock Estimation on Oil Palm Plantations and Oil Palm-Based Agroforestry in Gunung Mas Regency - Rosaprana, Wanella; Kuncahyo, Budi; Puspaningsih, Nining (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Central Kalimantan has one of the highest rates of deforestation and palm oil production in Indonesia. These changes have ecological impacts such as loss of animals, loss of water absorption functions, and increased carbon emissions. Agroforestry is a synergistic planting system between agricultural crops and forest stands to maintain the ecological balance. Sengons are legume plants that can be utilized in agroforestry systems. This study aimed to calculate the amount of belowground and aboveground carbon stocks on palm oil plantations and agroforestry lands consisting of palm oil and sengon trees in Manuhing and Rungan Barat districts. Belowground carbon consist of soil carbon, which is affected by the soil depth, bulk density, and soil C-organic value. Aboveground carbon consists of the sum of litter carbon, undergrowth carbon, and top stand vegetation carbon. Belowground carbon was measured using both disturbed and undisturbed methods. Litter and undergrowth carbon were measured using a destructive method, then top stand vegetation was measured by the allometric equations using breast height diameter. The comparison from all carbon pool shows that the palm oil plantations (2106,520 tons/ha) was higher than agroforestry lands (1834,734 tons/ha). This difference is strongly influenced by the potential of the different in belowground carbon stock for each land-use type. The highest potential carbon stock from this study was owned by belowground carbon stock. In the Manuhing district, belowground carbon stock was led by agroforestry lands (1786,907 tons/ha), whereas in the Rungan Barat district was led by palm oil plantations (1756,291 tons/ha).